Upaya Meningkatkan Kemampuan Menulis Teks Ulasan Dengan Menggunakan Media Padlet - Ratih, I Dewa Ayu Gede Suwari; Indriani, Made Sri; Nurjaya, I Gede (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study aims to describe the process of learning review texts through the use of Padlet media for class VIII students of SMP Negeri 2 Petang, describe the increase in learning outcomes for class VIII students of SMP Negeri 2 Petang in writing review texts through the use of Padlet media, describe the responses of class VIII students of SMP Negeri 2 Petang on the use of Padlet media in learning to write review texts. This study used a classroom action research design with Indonesian subject teachers and class VIII students of SMP Negeri 2 Petang, as well as student activity objects, learning outcomes of writing review texts, and student responses. Methods of data collection using observation, tests, and questionnaires and analyzed using descriptive qualitative and quantitative descriptive data analysis techniques. The results of the study show that (1) the proper learning process in using Padlet media emphasizes the procedure for writing review texts, good vocabulary, sentences, and spelling, (2) using Padlet media can improve the ability to write review texts. In the pre-action the average score of students was 62.5 categories (enough), cycle 1 obtained an average score of 73 categories (good), while cycle II the average student score was 88.7 categories (very good), (3 ) very positive student responses to the use of Padlet media. In cycle I, an average of 43.4 (positive) was obtained, while in cycle II, an average of 46.5 (very positive) was obtained.